The Extended Distributional Areas of Solanum lasiocarpum (Solanaceae) in Sumatra, Indonesia - Muhammad Rifqi Hariri; Arifin Surya Dwipa Irsyam; Rina Ratnasih Irwanto; Kusnadi Kusnadi (Pusat Penelitian dan Pengembangan Hutan, 2022)
Solanum is one of Solanaceae's largest genera, where some species are usually used as food and medicine. Until recently, 15 species of Solanum subg. Leptostemonum has been listed in Sumatra, Indonesia. Solanum lasiocarpum Dunal is a native Leptostemonum found in Indonesia. S. lasiocarpum was only recorded in Northern Sumatra by several botanists. In 2019, S. lasiocarpum was also reported from Bengkulu, but there were still doubts about these findings. During the expedition of invasive alien plant species in Padang Bindu, Sumatra Selatan, in May 2021, we discovered S. lasiocarpum with different noticeable characteristics from S. lasiocarpum, which was previously found in Bengkulu. Detailed examination of the morphological characters, our study revealed that that species was S. lasiocarpum. This finding suggested an extended distributional record for S. lasiocarpum in Sumatra.